Progressive Failure Mechanism of Shield Tunnel Face in Complex Urban Geological Environment - Huang, Qingfei; Han, Kaihang (Buildings (Basel), 2024)
The construction of multiple tunnels across inland rivers has had a significant influence on the improvement of the transportation infrastructure. The technology for constructing tunnels is progressing towards the development of larger cross-sections, longer distances, and the ability to withstand high hydraulic pressure in complex hydrogeological conditions, including high-permeability strata. In order to ensure the face stability of shield tunnels under high hydraulic pressure that crosses a fault fracture zone, it is necessary to study the progressive failure mechanism of shield tunnel faces induced by high hydraulic pressure seepage. This paper employs finite element numerical simulation software to methodically examine the variation in the characteristics of the water seepage field, limiting support force, and face stability failure mode of shield tunnels passing through fault fracture zones with high hydraulic pressure under varying fault fracture width zones. The results show that the formation hydraulic gradient will progressively widen when the tunnel face is located within the undisturbed rock mass and is advanced towards the area of fault fracture. This will raise the likelihood of instability in the shield tunnel and progressively raise the limiting support force on the tunnel face. Moreover, as the tunnel face nears the region of fault fracture within the undisturbed rock mass, the damage range increases gradually. In addition, due to the increase in seepage force, the angle between the failure area and the horizontal plane becomes more and more gentle. On the contrary, as the tunnel’s face moves closer to the undisturbed rock mass from the region of the fault fracture, the damage range gradually decreases, and the dip angle between the damage area and the horizontal plane becomes steeper and steeper due to the decreasing seepage force in the process. The study findings presented in this work are highly significant, both theoretically and practically, for the design and management of safety.